Epidemiology, clinical characteristics, and treatment of severe fever with thrombocytopenia syndrome - Jia-Chen Li; Jing Zhao; Hao Li; Li-Qun Fang; Wei Liu (Infectious Medicine, 2022)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease caused by a novel phlebovirus (SFTS virus, SFTSV) in the family Phenuiviridae of the order Bunyavirales. The disease causes a wide spectrum of clinical signs and symptoms, ranging from mild febrile disease accompanied by thrombocytopenia and/or leukocytopenia to hemorrhagic fever, encephalitis, multiple organ failure, and death. SFTS was first identified in China and was subsequently reported in South Korea and Japan. The case-fatality rate ranges from 2.7% to 45.7%. Older age has been consistently shown to be the most important predictor of adverse disease outcomes. Older age exacerbates disease mainly through dysregulation of host immune cells and uncontrolled inflammatory responses. Tick-to-human transmission is the primary route of human infection with SFTSV, and Haemaphysalis longicornis is the primary tick vector of SFTSV. Despite its high case-fatality rate, vaccines and antiviral therapies for SFTS are not currently available. The therapeutic efficacies of several antiviral agents against SFTSV are currently being evaluated. Ribavirin was initially identified as a potential antiviral therapy for SFTS but was subsequently found to inefficiently improve disease outcomes, especially among patients with high viral loads. Favipiravir (T705) decreased both time to clinical improvement and mortality when administered early in patients with low viral loads. Anti-inflammatory agents including corticosteroids have been proposed to play therapeutic roles. However, the efficacy of other therapeutic modalities, such as convalescent plasma, is not yet clear.